PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN DENGAN PERPUTARAN KAS SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KEUANGAN PT. ACE HARDWARE INDONESIA, Tahun 20 - Tjahjo Nugroho, Judianto; Winda Febriyanti, Nur (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
This study aims to determine the effect of receivables turnover and inventory turnover on the company's financial performance with cash turnover as the intervening variable. The study used a quantitative approach with the type of causal associative research. The Data used is the financial data of PT Ace Hardware Indonesia Tbk for the period 2018 to 2022. The data analysis in this study used Partial Least Square – Structural Equation Modeling (PLS – SEM) with STATCAL software updated September 17, 2022. The results showed that inventory turnover significantly affect financial performance directly, but there is no significant variable that affects financial performance through cash turnover